PROBLEMATIKA PIDANA HUKUMAN MATI DALAM PERSPEKTIF SISTEM PEMASYARAKATAN - Pratama, Ravi Agsel; Subroto, Mitro (Universitas Halu Oleo, 2021)
Indonesia, which is trying to reorganize in the field of criminal law reform, cannot be separated from the issue of the death penalty. Of course this will have an impact on the context of the formation of the new Criminal Code (KUHP) made by the Indonesian people themselves which have long been aspired to. In addition, the increasing number of death penalty sentences handed down against criminals makes the author interested in studying the existence of capital punishment sanctions, especially in the aspect of human rights and also in the perspective of the correctional system. This is because the death penalty has conflicting values and concepts in the Constitution and the Indonesian Correctional System. In this study, the researcher conducted a normative analysis which resulted in the conclusion that convicts on death row would be able to carry out the coaching program without coercion.Â